1997
DOI: 10.1103/physreve.56.6869
|View full text |Cite
|
Sign up to set email alerts
|

Further insights on dynamic morphological transitions in quasi-two-dimensional electrodeposition

Abstract: Dynamic morphological transitions in thin-layer electrodeposits obtained from copper sulphate solutions have been studied. The chemical composition of the electrodeposits indicates that they appear as a consequence of the competition between copper and cuprous oxide formation. In addition, the Ohmic control of the process is verified at initial stages of the deposit growth. At higher deposit developments, gravity-induced convection currents play a role in the control of the whole process and affect the positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…Under higher growth driving force, deposits were grown at a faster rate and the smaller grains were usually obtained [10,29]. Moreover, under different driving force, the distribution of local electric field intensity and the ion immigration at the growth front should be different, and the morphologies of deposits should vary accordingly [12, 13,17,29,31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under higher growth driving force, deposits were grown at a faster rate and the smaller grains were usually obtained [10,29]. Moreover, under different driving force, the distribution of local electric field intensity and the ion immigration at the growth front should be different, and the morphologies of deposits should vary accordingly [12, 13,17,29,31].…”
Section: Resultsmentioning
confidence: 99%
“…Afterwards, other researchers found that, besides the fractal morphology, the dense branching and dendritic patterns in the electrochemical deposition procedure of zinc could also be obtained under different experimental conditions [6,7]. Recently, it was distinctly understood that the patterns of electrochemical deposits were very sensitive to the materials studied and the experimental conditions [8][9][10][11][12][13][14][15]. Based on the analysis of the relationship between deposits patterns and experiment parameters, Trigueros and Sagues et al developed a rather complicated ''morphology phase diagrams'' [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…As the reduction of cuprous ions into copper metal is favoured in alkaline medium, this transition can be attributed to the movement of an acidic front towards the deposit [39]. This example of morphological transition was given on tantalum as it is an attractive metal for microelectronics but this behaviour is also found on copper.…”
Section: Dendritic Growth On a Tantalum Electrodementioning
confidence: 94%
“…For a copper sulfate solution, the authors have shown [34,38,39] that the formation of cuprous oxide (Cu 2 O) is often responsible for the transition. As the reduction of cuprous ions into copper metal is favoured in alkaline medium, this transition can be attributed to the movement of an acidic front towards the deposit [39].…”
Section: Dendritic Growth On a Tantalum Electrodementioning
confidence: 98%
“…Many authors have reported the quasi-two-dimensional growth of metallic electrodeposits, particularly for copper [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] and zinc [16][17][18][19][20][21][22][23][24][25], and other metals [26][27][28][29][30][31]. The typical patterns observed so far are stringy, dendritic, open ramified, dense branching morphology (DBM), and diffusion limited aggregation (DLA), etc, depending on the growing conditions, such as applied voltage, concentration of the solution and thickness of the electrolyte layer.…”
Section: Introductionmentioning
confidence: 95%